One-Pot Synthesis of Aminated Bimodal Mesoporous Silica Nanoparticles as Silver-Embedded Antibacterial Nanocarriers and CO 2 Capture Sorbents - Yun Li; Amit K. Tiwari; Jingyi Sandy Ng; Geok Leng Seah; Hong Kit Lim; Teeraporn Suteewong; Chor Yong Tay; Yeng Ming Lam; Kwan Wee Tan (ACS Applied Materials & Interfaces, 2022)
. Our results provide an enhanced understanding of the structure formation of multiscale mesoporous inorganic materials that are desirable for numerous applications such as carbon sequestration, water remediation, and biomedical-related applications.
Keywords: Mesoporous Materials and Catalysis; Zeolite Catalysis and Synthesis; Covalent Organic Framework Applications